1-C-phosphonomethyl- and 1-C-difluorophosphonomethyl-1, 4-imino-l-arabinitols as Galf transferase inhibitors: A comparison. (22nd May 2018) - Cocaud, Chloé; Zheng, Ruixiang B.; Lowary, Todd L.; Poisson, Thomas; Pannecoucke, Xavier; Nicolas, Cyril; Martin, Olivier R.
Abstract: The convenient preparation of iminopentitol derivatives, based on a 1, 4-dideoxy-1, 4-imino-l -arabinitol scaffold carrying β-phosphono(difluoromethyl) or β-phosphonomethyl appendages, as Gal f -1P mimics, is reported. The compounds were tested for their ability to inhibit GlfT2, a vital galactofuranosyltransferase involved in the cell wall biosynthesis of mycobacteria. Interestingly, the Gal f -1P mimics lacking a fluorine atom (7 and8 ) were very poor inhibitors, showing less than 20% inhibition of GlfT2, whereas compounds2 and3, which contains a difluoromethylenephosphonate moiety were more potent inhibitors. Compound3 that is fully deprotected was the most potent showing a significant IC50 value (0.9 mm ), despite the absence of the diphosphate linkage present in the parent sugar nucleotide. This study paves the way to the synthesis of more complex β-phosphonomethyl-imino-l -arabinitol derivatives as simplified mimics of UDP-α-d -Gal f . Graphical abstract: Highlights: Synthesis of imino-l -arabinitols with (non)-fluorinated phosphonomethyl appendages. The compounds behave as Gal f -1P mimics and inhibitors of GlfT2. Gal f -1P mimics with a difluoromethylenephosphonate moiety are more potent inhibitors. The study paves the way to the synthesis of more complex mimics of UDP-α-d -Gal f .